2022
DOI: 10.1017/s0007114522002458
|View full text |Cite
|
Sign up to set email alerts
|

Adequate levels of dietary sulphur amino acids impart improved liver and gut health in juvenile yellowtail kingfish (Seriola lalandi)

Abstract: The sulphur amino acids methionine and cysteine and their derivative taurine are metabolically active molecules with interlinked roles in nutritional requirements. Deficiencies in these nutrients are linked to poor growth and health; however, the impacts of these deficiencies on organ structure and function are largely unknown. This study examined the effects of dietary methionine, cysteine, and taurine fed at different levels on yellowtail kingfish liver histology and surface colour, plasma biochemistry, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
1
1
0
Order By: Relevance
“…Meanwhile, non-specific serum immune parameters were improved, and the levels of immunoglobulins (IgM, IgA, and IgG), complement 3, complement 4, and LZM activity were increased, which may help the fish cope with oxidative stress and immunity reduction caused by low-fishmeal diets, thus improving growth performance. Our findings are similar to those found in Seriola lalandi ( 47 ) and Scophthalmus maximus L ( 48 ), where cysteine enhanced growth performance by improving resistance to oxidative stress and intestine immunity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Meanwhile, non-specific serum immune parameters were improved, and the levels of immunoglobulins (IgM, IgA, and IgG), complement 3, complement 4, and LZM activity were increased, which may help the fish cope with oxidative stress and immunity reduction caused by low-fishmeal diets, thus improving growth performance. Our findings are similar to those found in Seriola lalandi ( 47 ) and Scophthalmus maximus L ( 48 ), where cysteine enhanced growth performance by improving resistance to oxidative stress and intestine immunity.…”
Section: Discussionsupporting
confidence: 89%
“…Oxidative stress and immune capacity reduction caused by low fishmeal content are the main reasons for reduced growth performance ( 8 , 9 , 46 ). In the present study, there were many reasons that cysteine supplementation improved the growth performance of golden pompano in low fishmeal conditions, such as the increased abundance and diversity of gut microbes ( 31 ), increased antioxidant capacity ( 47 , 48 ), and improved immune ability ( 27 ). Our results showed that dietary supplementation with 0.6%–1.2% cysteine could increase the activity of serum antioxidant enzymes (T-AOC, CAT, and GSH-PX) and decrease the serum MDA and ROS levels in juvenile golden pompano.…”
Section: Discussionmentioning
confidence: 80%